Health Informatics: A Challenge for Nurses in Public Health in Rural Mexico - Perezmitre, Erika Lozada; Gómez Flores; Miguel Ivan; Lokmic-Tomkins, Zerina; Landeros-Olvera, Erick; von Gerich Hanna; Galicia Aguilar, Rosa-María (Netherlands, 2025)
Health informatics has significantly advanced global technology, yet challenges persist in public health and rural nursing in Mexico due to social inequalities, limited technology access, and suboptimal infrastructure, compounded by the absence of nurse informaticians as viable career options. Overcoming these barriers necessitates international collaboration, empowering Mexican nurses to contribute to universal health access and advocate for health equity. Interventions must extend beyond nursing curricula to existing workforces, ensuring they can address the needs of vulnerable populations in Mexico. Long-term international support is crucial to bridge these gaps and unleash the full potential of Mexican nurses in influencing global health.
Innovation in Applied Nursing Informatics